Redefining commitment and attractive alternatives: re-examining the investment model - Ratcliffe, Gary Cole (Kansas State University, 2013)
The current study tested Rusbult’s (1980) investment model of relationship commitment. Specifically, this study used data from 875 married individuals to examine the associations between marital satisfaction, alcohol use, video gaming, relationship length, and the presence of children on two types of relationship commitment: psychological attachment and behavioral intent. The results indicate that alcohol use, video gaming, relationship length, and presence of children are not significantly associated with psychological attachment or behavioral intent. However, findings in the current study do suggest that psychological attachment and behavioral intent are independent constructs and should be examined separately. Furthermore, neuroticism and religiosity did predict individual’s behavioral intent, but not psychological attachment.
Keywords: Psychology; Psychology (0621)